Democratically included? A systematic literature review on voter turnout of people with intellectual disabilities - Boman, Björn; Rosenberg, Jonas Hultin (Frontiers in Political Science, 2024)
The extent to which people with intellectual disabilities (ID) are voting is an under-researched area. In order to fill this gap, we conducted a systematic literature review with a focus on voter turnout and democratic inclusiveness among people with ID. In total, we found N = 9 studies that met our inclusion criteria, all of which were based on samples from Western countries such as Croatia, Ireland, Netherlands, Sweden, Switzerland, UK and US. Our findings suggest that people with ID have substantially lower voter turnout than ordinary voters. Constraining factors for voting and other instances of democratic inclusion include educational limitations and physical obstacles at ballot places, as well as being under full guardianship. On the other hand, living in a household with a voter constitutes a facilitating factor. Because of the limited number of studies, we suggest that more basic quantitative and qualitative research in many countries ought to be conducted.